Hubungan Lingkungan Pengasuhan dan Pekerjaan Ibu terhadap Perkembangan Bayi 6-12 Bulan - Sara Herlina (Jurnal Kesmas Asclepius, 2019)
The purpose of this study was to determine the relationship between the caregiving environment and mother's work on infant development. The design of this study was cross sectional. The results of the study were obtained by the majority of good care environment as much as 39.7%, mothers did not work as much as 60.9%, and babies experienced normal development as much as 52.3%. Chi square test results of the relationship between the caregiving environment for infant development obtained p value <0.005, that is <0,000 the relationship between maternal work and infant development obtained p value <0.005, 0.003. Conclusion, there is a relationship between the care environment and mother's work on the development of the baby. Keywords: Caregiving Environment, Mother's Work, Development